Ethical Research Dilemmas and Their Implications In English Language Teaching Studies - Daniel Ginting (Universitas Muhammadiyah Kalimantan Timur, 2022)
Researchers across the disciplines, including those whose passions are in English teaching studies, are always challenged to continuously contribute their research findings to the development of science. However, ethical considerations must be adhered to when they involve humans as participants in their study. Ethical dilemmas, even though they are considered important, are still rarely discussed. Thus, depicting the sketch of a comprehensive configuration of ethical dimensions is extremely needed for ESL researchers to serve as a guidance to carry out their research. This paper concludes with some ethical implications for researchers to carry out research ethically